PKM Evaluasi Pada Implementasi Pelaporan Keuangan Organisasi Nirlaba (PSAK 45) Pada Yayasan Untuk Segala Bangsa Dan Yayasan Pondok Akar - Yandira, Cesya Sevie; Herawati, Heti; Andrianto, Toni (Jurnal Abdimas Dedikasi Kesatuan, 2021)
In Indonesia the non-profit society is an organization that has organizational structure that has a vested interest in social, religious and humanitarian welfare. Financial reporting becomes a tool for recognition, presentation and disclosure following other applicable standards. Financial reporting has becom an important part along with the organization’s expanding growth ang development. The purpose of this study is to knoe the financial reports of Yayasan Untuk Segala Bangsa and Yayasan Pondok Akar whether the financial report has been appropriated and implemented in full PSAK No. 45. The author will do research in Yayasan Untuk Segala Bangsa and Yayasan Pondok Akar located on Jl. Jurang No. 28, Desa Tugu Utara Cisarua. This study states that the creation of financial report on Yayasan Untuk Segala Bangsa makes nothing more than a balance sheet and income statement or activity report, and on Yayasan Pondok Akar writes only cash incomes and expenitures, and has not yet produced a financial report at all. This is because of the lack of skilful human resources. The presentation of foundation’s financial statements Yayasan Untuk Segala Bangsa has been in accordance with the term of PSAK No. 45 but not completely, as the foundation has not created the cash flow and record statements of the financial statements, and there are points of specification separation of neto assets that has not been done by the foundation. Yayasan Pondok akar has not applied PSAK No.45 and it may be said that it has not been in full harmony.   Keywords: foundation, PSAK 45, non-profit organizations, financial reports